Sulūk wa-Iḥyā’ al-Ḥadīth fī al-Ḥaram al-Jāmi‘ī al-Akhḍar fī Bī’at Jāmi‘at Sharīf Hidāyatullāh Jākartā - Salim, Hasan Basri; Zahasfan, Alvian Iqbal; Hidayatulloh, Muhammad; Fatihunnada, Fatihunnada; Kamaliah, Mawritsa; Ummah, Sayidatul (Fakultas Dirasat Islamiyah, Univitas Islam Negeri (UIN) Syarif Hidayatullah Jakarta, 2025)
This study examines the Green Campus practices of academics at UIN Syarif Hidayatullah Jakarta by exploring the underlying motives that drive their environmental attitudes and actions. Unlike earlier Living Hadith studies that documented eco-friendly behavior as acts of worship, this research adopts a qualitative phenomenological approach using observation, documentation, and interviews to uncover the meaning behind such practices. The findings show that the academic community actively supports sustainability through energy conservation, waste reduction, recycling initiatives, the use of eco-friendly transportation, and the promotion of responsible lifestyle choices, demonstrating a strong institutional commitment to environmental stewardship. Notably, their motivation is rooted more in rational and modern ecological awareness than in strict textual adherence to religious teachings. In this context, hadith functions not as a primary normative source, but as a reinforcement of universal values aligned with environmental ethics. Cleanliness, for example, has become an internalized social norm, practiced not out of command, but out of logical necessity. This reflects a selective and contextual engagement with religious texts, where Islamic teachings are harmonized with global sustainability values. Environmental motivation is thus multidimensional: religious, social, and ecological.